2014
DOI: 10.1117/1.jbo.19.4.046005
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical whole body time domain fluorescence lifetime multiplexing of fluorescent proteins

Abstract: Abstract. The application of time domain (TD) fluorescence lifetime multiplexing for the detection of fluorescent proteins (FPs) in whole animals, in the presence of a strong background tissue autofluorescence and excitation light leakage is discussed. Tissue autofluorescence (AF) exhibits a nonexponential temporal response, distinct from the mono-exponential decay of FPs. This allows a direct separation of FP fluorescence from AF using a dual basis function approach. We establish the detection limits of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…2j), allows the use of a dual basis function approach (18,21) to eliminate AF from the transmission TD fluorescence images. In this approach, the decay portion of the TD fluorescence was fit with a dual-basis function (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2j), allows the use of a dual basis function approach (18,21) to eliminate AF from the transmission TD fluorescence images. In this approach, the decay portion of the TD fluorescence was fit with a dual-basis function (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…2f,g,j. The dual basis function approach allows a dramatic increase in the contrast to background ratio (defined as the ratio of either the CW intensity or decay amplitude inside the lungs to that of the surrounding tissue (21)) of more than 20-fold by separating the iRFP720 fluorescence and tissue AF. Unlike the CW images (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, time-dependent methods may provide more information for mathematical reconstruction to identify 3-D fluorescent target location and strength [18], [19]. In addition, time-dependent measurements offer the only opportunity for 3-D reconstruction of fluorescent lifetime which can be developed for sensing tissue environments, receptor-probe interactions, and evaluating molecular kinetics in vivo [20]- [23]. However, these time-dependent methods, whether are conducted with pulsed excitation light in time-domain (TD) measurements or with modulated excitation light in frequency-domain (FD) measurements, require more complicated instrumentation, are more greatly influenced by noise, and have longer data acquisition times than CW technique.…”
Section: Introductionmentioning
confidence: 99%
“…17 To address this limitation, we and others have explored the idea of jointly using both fluorophore emission lifetime and spectral data in FMT. [18][19][20][21][22] In particular, organic NIR fluorophores typically have lifetimes on the order of 0.5 to 2 ns (with emission lifetimes usually being shorter at longer wavelengths). Our previous studies 23,24 suggested that joint use of spectral and temporal data provides more accurate demixing performance than either alone.…”
Section: Introductionmentioning
confidence: 99%